DETERMINING THE KNOWLEDGE LEVEL OF PUPILS IN THE INFORMATION SYSTEM OF "SMART SCHOOL" - Masharipov, Sanatbek Atanazarovich; Raximova, Laylo Saparbayevna; Axmedova, Xolisa Ilhomovna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
At a time when current information technologies are rapidly developing, the effectiveness of the quality of education in secondary schools, the transparency of the teacher evaluation system and the analysis of several other indicators with the help of artificial intelligence are the urgent issues of the day. In this method of analysis, initially the value is entered by school experts. This value consists of a pupil in a certain category among pupils and his grades. The term category refers to various criteria, such as pupils with different levels of mental activity, pupils who are learning poorly, who are missing a lot of lessons, and the level of learning is high or low within the specified subjects or topics. The "Smart School" information system forms arrays consisting of the number of grades and grades of pupils according to the criteria entered by experts, and has the ability to sort the values that are similar to the entered value. The solution to the problem posed in this article is explained mathematically and practically. Based on the proposed mathematical models, the business process was modeled, a business process software product was developed, and statistical data was obtained.